Moral gravity : staying together at the end of the world - Hill, David W. (Lecturer) (Bristol shorts research., 2022)
This radical book unsettles how we think about taking responsibility for environmental catastrophe. Going beyond both hopelessness and false hope as responses to climate change, Hill envisions a society that does not centre human beings at its core and calls for sustaining a coexistence of animals, plants and minerals bound by one planet.